Perkawinan beda agama : menakar nilai-nilai keadilan Kompilasi hukum Islam - Karsayuda, M., 1954- (Yogyakarta : Total Media Yogyakarta, 2006)
Interfaith marriage in the context of justice in the compilation of Islamic laws in Indonesia
Revision of the author's thesis (S2)--IAIN Antasari, Banjarmasin, 2005
Includes bibliographical references (p. 191-200)
Keywords: Interfaith marriage -- Indonesia; Interfaith marriage (Islamic law) -- Indonesia; Islam and justice -- Indonesia